Analisa Perawatan Berbasis Keandalan pada Sistem Bahan Bakar Mesin Utama KMP. Bontoharu - Risna Imanuell; Mohammad Lutfi (Pusat Penelitian dan Pengabdian kepada Masyarakat, Politeknik Negeri Balikpapan, 2019)
This study determines the prone components and the mean time to failure of KMP. Bontoharu. The method used in this research is the qualitative analysis, which comprises the failure mode, effect, analysis (FMECA), fault tree analysis (FTA), and quantitative analysis using Weibull distribution to determine the mean time to failure (MTTF) value. The risk method based inspection and maintenance is used to determine the value of equipment risk and maintenance scheduling model, and the inspection method used is visual check. The results revealed that the value of MTTF filter was 194 hours, separator was 502 hours, and pipe was 2508 hours. Filters and separators have the highest level of risk, while the mainframe, daily trays, transfer pumps, feed pumps, injection pumps, and injector service tanks have medium risk levels. Keywords: fuel system, Reliability, FMECA, FTA, Maintenance